Non-alcoholic fatty liver disease, metabolic syndrome and subclinical cardiovascular changes in the general population. Issue 12 (10th April 2014) - Kim, Nan Hee; Park, Juri; Kim, Seong Hwan; Kim, Yong Hyun; Kim, Dong Hyuk; Cho, Goo-Yeong; Baik, Inkyung; Lim, Hong Euy; Kim, Eung Ju; Na, Jin Oh; Lee, Jung Bok; Lee, Seung Ku; et al.
Abstract : Objective: The effect of non-alcoholic fatty liver disease (NAFLD) on cardiovascular system remains controversial. We investigated the independent contribution of NAFLD to cardiovascular structure and function in the general population. Methods: A total of 1886 participants without known cardiovascular disease were enrolled from the Korean Genome Epidemiology Study. The participants were divided into four groups, based on the presence of NAFLD, metabolic syndrome (MetS), neither or both. NAFLD was diagnosed by CT. Changes in cardiovascular structure and function were assessed by tissue Doppler imaging (TDI) echocardiography, carotid ultrasound and brachial-ankle pulse wave velocity (baPWV). Results: In multivariate analyses, subjects with both NAFLD and MetS had a higher E/Ea ratio and baPWV, as well as a lower TDI Ea velocity (all p<0.001) than those with neither NAFLD nor MetS. Subjects with either NAFLD or MetS also showed significant differences in TDI Ea velocity and baPWV (all p<0.05). However, no significant differences of carotid intima-media thickness (CIMT) values were seen among the four groups. Multivariate linear regression revealed that both NAFLD and MetS were independent predictors of TDI Ea velocity and baPWV (all p<0.001). Both MetS and NAFLD were not a determinant of CIMT. Conclusions: NAFLD was associated with early alterations of cardiovascular system, independent of established cardiovascular risk factors and MetS.